Color monitors: the black face of technology in America - Kevorkian, Martin (Cornell University Press, 2006)
"Color Monitors looks at a particular subset of imagined computer use, focusing on scenarios that demand from the person at the keyboard an intimate technical knowledge. My research has uncovered a peculiar pattern: race comes into sharp relief when.